A comparison of experiences of care and expressed emotion among caregivers of young people with first-episode psychosis or borderline personality disorder features. (September 2022) - Cotton, Sue M; Betts, Jennifer K; Eleftheriadis, Dina; Filia, Kate; Seigerman, Mirra; Rayner, Victoria K; McKechnie, Ben; Hulbert, Carol Anne; McCutcheon, Louise; Jovev, Martina; Bendall, Sarah; Burke, Emma; et al.
Objective: Caregivers of individuals with severe mental illness often experience significant negative experiences of care, which can be associated with higher levels of expressed emotion. Expressed emotion is potentially a modifiable target early in the course of illness, which might improve outcomes for caregivers and patients. However, expressed emotion and caregiver experiences in the early stages of disorders might be moderated by the type of severe mental illness. The aim was to determine whether experiences of the caregiver role and expressed emotion differ in caregivers of young people with first-episode psychosis versus young people with 'first-presentation' borderline personality disorder features. Method: Secondary analysis of baseline (pre-treatment) data from three clinical trials focused on improving caregiver outcomes for young people with first-episode psychosis and young people with borderline personality disorder features was conducted (ACTRN12616000968471, ACTRN12616000304437, ACTRN12618000616279). Caregivers completed self-report measures of experiences of the caregiver role and expressed emotion. Multivariate generalised linear models and moderation analyses were used to determine group differences. Results: Data were available for 265 caregivers. Higher levels of negative experiences and expressed emotion, and stronger correlations between negative experiences and expressed emotion domains, were found in caregivers of young people with borderline personality disorder than first-episode psychosis. Caregiver group (borderline personality disorder, first-episode psychosis) moderated the relationship between expressed emotion and caregiver experiences in the domains of need to provide backup and positive personal experiences. Conclusion: Caregivers of young people with borderline personality disorder experience higher levels of negative experiences related to their role and expressed emotion compared with caregivers of young people with first-episode psychosis. The mechanisms underpinning associations between caregiver experiences and expressed emotion differ between these two caregiver groups, indicating that different supports are needed. For borderline personality disorder caregivers, emotional over-involvement is associated with both negative and positive experiences, so a more detailed understanding of the nature of emotional over-involvement for each relationship is required to guide action.